Sistema de aquisição de baixo custo para um dinamômetro biomédico - Cortez, Paulo José Oliveira; Machado, Sandro Oliveira; Rosa, Renato; Valenti, Vitor Engrácia [UNESP]; Tomazini, José Elias [UNESP] (My University, 2013)
Objective: to create a purchasing system for optimizing a low cost device fabrication itself. Method: For this purpose was designed a system which is powered by a 12V battery center. The full bridge of "Wheatstone" is powered by the central battery set to 9V. Results: The sign of the strain has a range of 0 to 30 mV which is amplified filtered by a signal conditioner own manufacturing using an LM 324. The electrical signal then passes to vary from 0 to5V which will be processed in an analog input of PIC microcontroller. Tests for the registration and interpretation of data are through software MyOpenLab. Conclusion: The work is in progress and initial results suggest that the system will be able to measure muscular strength accurately and cost-effective.

Objetivo: criar um Sistema de Aquisição de baixo custo, otimizando um dispositivo de fabricação própria. Método: Para tanto, foi idealizado um sistema dedicado, o qual é alimentado por uma bateria central de 12V. A ponte completa de “Wheatstone” é alimentada pela bateria central, regulada em 9V. Resultados: O sinal dos extensômetros apresenta uma variação de 0 a 30 mV, o qual é amplificado e filtrado por um Condicionador de Sinais de fabricação própria, usando um LM 324. O sinal elétrico então passa a variar de 0 a 5V, que serão tratados em uma entrada analógica de um Microcontrolador PIC. Os testes para registro e interpretação dos dados ocorrem através do software MyOpenLab. Conclusão: O trabalho está em andamento e os primeiros resultados sugerem que o sistema será capaz de mensurar a força muscular de forma precisa e com custo reduzido.
Acquisition system of a low cost biomedical dynamometer